Addressing the Burnout and Shortage of Nurses in the Philippines - Rowalt Alibudbud MD (SAGE Publishing, 2023)
Burnout among Filipino nurses poses a significant threat to an understaffed Philippine healthcare system, leading to resignations, change of profession, and migration to other countries, thereby exacerbating the shortage in the local nursing sector. While workplace mental health programs and interventions can help alleviate burnout, it is crucial to address the structural factors contributing to burnout among Filipino nurses, such as low salaries, delayed benefits, understaffing, overwork, and job insecurity. Therefore, mobilizing existing resources and improving policies are critical steps that need to be taken to effectively address burnout among nurses. Measures such as increasing salaries, timely provision of benefits, and filling vacant government regular positions can contribute to improving the working conditions for nurses in the Philippines. Moreover, by undertaking these measures, the Philippines can advance just working and living conditions for nurses, while also mitigating the challenges posed by the shortage of nurses within its healthcare system.